"A New Slavery of Caste": An Evaluation of President Woodrow Wilson with Regard to Race - Depew, Jennifer (My University, 2017)
The presidency of Woodrow Wilson has been traditionally considered successful due to his administration’s progressive legislation and leadership during World War I. Recently, his positive reputation has been challenged on the grounds of his racist views. This paper argues that these challenges are legitimate by first establishing criteria for evaluating presidents based on constitutional rights and values, and then by examining the Wilson administration’s relationships to two race-based crises: the segregation of the civil service and mob violence. Wilson’s bigotry led him to consistently make decisions that negatively impacted the lives and livelihoods of millions of African Americans. His unwillingness to uphold the individual rights and equal protections promised to all Americans, regardless of race, represents a fundamental failure of his presidential duty. Failures like these should weigh heavily in any meaningful evaluation of presidential success.
Oshkosh Scholar, Volume XI
Keywords: United States Presidents; African Americans; Civil rights